Evolution of Robotic Technology in Urologic Surgery - Singla, Nirmish (Urol Listy, 2014)
Over the last 25 years, the field of urology has seen the advent and evolution of minimally invasive surgical techniques. The robot in particular has been shown to be safe and efficacious in managing malignancies. More recently its application has been expanded to benign urological conditions. While some robotic applications have been well established, others remain at varying stages of evolution. Relative to open approaches, the robot has been shown to enhance intraoperative visualization and precision, mitigate surgeon tremor, hasten post-operative recovery, and shorten length of hospital stay for certain indications; however, it has also been associated with higher costs, longer operative times, and limited outcomes data. We review the evolution of robotic applications within urology and speculate on the future directions and implications within the field.